Chemical nociception in the jejunum induced by capsaicin. Issue 8 (9th July 2004) - Schmidt, B; Hammer, J; Holzer, P; Hammer, H F
Abstract : Background and aims: Chemonociception in the human small intestine has not been studied extensively. Although capsaicin can cause intestinal sensations, it is not known if this is due to stimulation of chemoreceptors or to motor changes. Our aims were to evaluate motor activity during capsaicin induced nociception and to compare qualities of jejunal nociception induced by capsaicin and mechanical distension. Methods: Twenty nine healthy subjects swallowed a tube with a perfusion site at the ligament of Treitz and, 7 cm distally, a barostat balloon. Phasic motor activity was measured around the perfusion site and the balloon. Capsaicin solutions (40, 200, and 400 μg/ml) 2.5 ml/min were perfused for 60 minutes or until severe discomfort occurred. A graded questionnaire for seven different sensations was completed every 10 minutes and after capsaicin perfusion was replaced by saline perfusion because of severe discomfort. Sensations arising from pressure controlled distensions were assessed before and after capsaicin perfusion when sensations had stopped (n = 19), or during capsaicin administration when no discomfort was reported (n = 5). Results: Capsaicin perfusion induced feelings of pressure, cramps, pain, and warmth. The quality and abdominal location of these sensations were similar to those induced by distension, except for warmth (p<0.01) and pressure (p<0.05). Seven of 12 subjects receiving 40 μg/ml capsaicin and all subjects receiving higher capsaicin concentrations developed discomfort. Perfusion had to be stopped after 55 (3.3), 15 (5.7), and 10 (2.2) minutes with 40, 200, and 400 μg/ml capsaicin, respectively, whereafter the sensations disappeared within 10 minutes. Repeated capsaicin (200 μg/ml) applications significantly reduced the time until discomfort occurred (p = 0.01). Jejunal tone was not altered by capsaicin but phasic activity proximal to the perfusion site was reduced during capsaicin induced discomfort (p<0.001). Pain thresholds during distensions were not different before and after capsaicin perfusion. Conclusion: Despite the similarities in abdominal localisation and perceptional quality of capsaicin and distension induced sensations, our results rule out the fact that abdominal discomfort evoked by capsaicin involves sensitisation of mechanoreceptors or an increase in phasic and tonic motor activity. Capsaicin evokes abdominal sensations by stimulation of chemoreceptors which proves the existence of chemonociception in the human small intestine.